2017
DOI: 10.1111/ors.12282
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous exposure incidents: a review of practice and awareness of current protocols at a Dental Faculty

Abstract: Background Research has shown that dental care providers (DCPs) and students are among the most vulnerable to accidental exposure to blood‐borne pathogens (BBPs). An exposure to BBPs can have detrimental effects on a DCP's professional and personal life. Objectives The aim of this study to study the prevalence and risk factors of sharps and needlestick injuries (NSIs) sustained by the staff and undergraduate dental students at the Faculty of Dentistry, University of Otago. Method A cross‐sectional survey among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…Similar to our study, needle stick injuries have been reported as the most common sharps injury at other dental schools 14,17,19,20,[24][25][26][27] and among dentists. 28 In this study, the majority of injuries occurred during administration of anaesthesia with a single instance occurring during assembling the syringe.…”
Section: Sharps and Percutaneous Injuriessupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to our study, needle stick injuries have been reported as the most common sharps injury at other dental schools 14,17,19,20,[24][25][26][27] and among dentists. 28 In this study, the majority of injuries occurred during administration of anaesthesia with a single instance occurring during assembling the syringe.…”
Section: Sharps and Percutaneous Injuriessupporting
confidence: 90%
“…While the majority of respondents were aware of the school's protocol for sharps injuries, only 41% adhered to it. Non-compliance with departmental sharps injury protocols and underreporting of sharps injuries seems to be a common practice among dental students 13,16 , [18][19][20]27 and dental health care workers. 28 Given that in this study, students admitted to not reporting sharps injuries, it is conceivable that underreporting of sharps injuries is still occurring.…”
Section: Adherence To Percutaneous Injury Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…It is certain that attention will continue to centre around personal protective equipment (PPE) for the face and the eyes. In contrast to earlier studies, compliance with the use of PPE at the UQ SoD was high and in line with current guidelines [20]. There may be bene ts for certain procedures where uid splashes are likely to move to a full face-shield [21].…”
Section: Discussionsupporting
confidence: 58%
“…It is likely that estimations of relative risk may reveal important effects of the student year level or the experience level of staff, relative to the complexity of the procedure being undertaken at the time of the accident. One would expect that more experienced clinical operators and support staff such as dental assistants would be less likely to sustain injuries as than novices to the particular workplace tasks [20]. Such aspects could be the focus for future studies.…”
Section: Discussionmentioning
confidence: 99%